Industrial Court: a court of equity and good conscience - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2010)
The Industrial Court is an inferior specialist tribunal adjudicating trade disputes that involve workers in the private sector. The court is not strictly confined to the administration of justice in accordance with the law, bit is an instrument for the dispensation of social justice according to equity and good conscience. Social justice and legal justice are two different concepts, although their common objective is to ensure that justice is done. Unlike the ordinary court of law, the functions of which are purely declaratory of the laws enacted by Parliament or upholding the doctrine of freedom of contract, among others, the Industrial Court is intended to provide speedy, fair and just resolutions to differences between parties to contracts of employment with considerations of equity and good conscience. The court has wider powers than an ordinary court of law in the prescription, recognition creation of rights, duties and obligations. Generally, the Industrial Court is to free workmen from contracts and obligations that were unfair and inequitable that the concept of social justice has been evolved. Having said the above, this article will highlight the dispensation of social justice in the Industrial Court.